If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12m + -13 = 9m + 38 Reorder the terms: -13 + 12m = 9m + 38 Reorder the terms: -13 + 12m = 38 + 9m Solving -13 + 12m = 38 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. -13 + 12m + -9m = 38 + 9m + -9m Combine like terms: 12m + -9m = 3m -13 + 3m = 38 + 9m + -9m Combine like terms: 9m + -9m = 0 -13 + 3m = 38 + 0 -13 + 3m = 38 Add '13' to each side of the equation. -13 + 13 + 3m = 38 + 13 Combine like terms: -13 + 13 = 0 0 + 3m = 38 + 13 3m = 38 + 13 Combine like terms: 38 + 13 = 51 3m = 51 Divide each side by '3'. m = 17 Simplifying m = 17
| 57+12m=7m+149 | | 13x+1=5x+49 | | 97+13m=5+17m | | 8y^2-y=-9 | | 11x=3x-56 | | 3x+9-7x=33 | | 5-y=10y-40 | | -3=4(-3)+6-(-3) | | 141000000/1.17 | | 6x+2-3x+2=9x-12 | | 9-5/3b=3 | | 2x^2-8x+8=98 | | 5(2+X)=3x-4 | | x^2/4x | | u^2-10u-21=0 | | 2x+4/3=x/7 | | 10+10M=0.35M | | 3m+71=11m+15 | | (u^2-8u-12)2=0 | | 14m+6=9m+91 | | 26x^2-30x-1147=0 | | 5-(2x-3)=-3+6 | | 9/30 | | 183-2m=4m | | 4X-3/5=X+3/10 | | X^2-10x+7=3 | | 135+4m=13m | | 7/8=5/8+9 | | 4X-3/5 | | 8m+78=11m | | 5-x+3x=29 | | 7-6(5y-y)=10(y-4) |